Blocked chains of governance: Using blockchain technology for carbon offset markets? - Round, Christopher; Visseren-Hamakers, Ingrid (Frontiers in Blockchain, 2022)
Information and communication technology (ICT) plays a critical role in environmental governance; however, research into power in governance has not focused on the impact of ICT. In this study, we analyze the use of blockchain in a voluntary carbon offset market using the “Four Faces of Power” (compulsory, institutional, structural, and productive) conceptual framework to determine how ICT can change the power dynamics within a network of stakeholders. Proponents have proposed that blockchain technology can solve several issues that carbon marketplaces and offsets face, such as cybersecurity, traceability, and financial liquidity. Despite these proposals, there is little scholarship on existing cases using blockchain in carbon offsets. We found that the use of blockchain technology by the company Veridium changed the compulsory and institutional power dynamics within the network of stakeholders it was a member of. Veridium’s choice to use blockchain technology was likely the result of structural and productive power dynamics surrounding the technology at the time. The power dynamics changed because the use of blockchain for Veridium’s carbon offset market caused additional stakeholders to join the network of stakeholders. The new stakeholders held greater compulsory and institutional power than Veridium. This research contributes to the limited scholarship focused on ICT and power in environmental governance. Empirically it contributes to the ongoing discussion around the possibilities of blockchain technology for climate policy.